2002
DOI: 10.1152/ajpheart.00371.2001
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training attenuates coronary smooth muscle phenotypic modulation and nuclear Ca2+ signaling

Abstract: Exercise training attenuates coronary smooth muscle phenotypic modulation and nuclear Ca 2ϩ signaling. Am J Physiol Heart Circ Physiol 283: H2397-H2410, 2002. First published July 26. 2002 10.1152/ajpheart.00371. 2001.-Physical inactivity is an independent risk factor for coronary heart disease, yet the mechanism(s) of exerciserelated cardioprotection remains unknown. We tested the hypothesis that coronary smooth muscle after exercise training would have decreased mitogen-induced phenotypic modulation and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 46 publications
4
22
0
Order By: Relevance
“…Similar results were obtained with cardiomyocytes [40] and coronary smooth muscle cells [41]. Therefore in the model, sarcoplasmic Ca 2+ removal (accounted for by a single time constant λ) was considered to be inhomogeneous, being highest just outside the nucleus.…”
Section: A 3-d Model For Amplitude Modulation Of Nuclear Ca 2+ Signalssupporting
confidence: 72%
“…Similar results were obtained with cardiomyocytes [40] and coronary smooth muscle cells [41]. Therefore in the model, sarcoplasmic Ca 2+ removal (accounted for by a single time constant λ) was considered to be inhomogeneous, being highest just outside the nucleus.…”
Section: A 3-d Model For Amplitude Modulation Of Nuclear Ca 2+ Signalssupporting
confidence: 72%
“…Our findings are in accordance with the existing literature. Indeed, Wamhoff et al (2002) reported, in adult female swine, that endurance exercise training enhances nuclear Ca 2+ regulation, possibly via SERCAs, localized very near the sarcolemma and along the rim of the nucleus to regulate Ca 2+ . Moreover, the fact that the ACh response was reduced by thapsigargin in the trained animals could suggest that the drug's effects on endothelium are greater than those on smooth muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the second aim of the study was to elucidate the possible mechanisms involved in vascular reactivity modifications after isometric exercise training. Current evidences suggest an involvement of several pathways such as endothelial NO (Sessa et al 1994;Kojda et al 2001;Hambrecht et al 2003), vasodilator prostaglandins (Koller et al 1995), ATP-dependent Ca 2+ pumps of the sarcoplasmic reticulum or endoplasmic reticulum (SERCA) (Wamhoff et al 2002), or calcium-sensitive potassium (K Ca ) channels (Chen et al 2001). Thus, an NO synthase blocker, a cyclooxygenase blocker, SERCA blockers, and K Ca channel inhibitors were used in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…Although limited, there is evidence that SMC nuclear Ca 2ϩ regulation can be altered in response to physiological or pathophysiological stimuli, eg, vascular disease, such that the amplitude and duration of nuclear Ca 2ϩ responses to contractile agonists are severely altered. 76,77 Whether this alters gene expression remains to be determined.…”
Section: Wamhoff Et Al Excitation-transcription Coupling 875mentioning
confidence: 99%